2009
DOI: 10.1007/s00062-009-8033-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stroke Therapy 1981–2009*

Abstract: This article includes a review of major intravenous and endovascular stroke trials, treatment options, and future aspects of acute stroke treatment in hemispheric and vertebrobasilar stroke. Since the invention of local intraarterial thrombolysis by Hermann Zeumer in 1981, acute stroke diagnostics and treatment have undergone dramatic improvement. This article addresses major topics in recent stroke treatment debates: optimization of patient selection, intravenous versus endovascular therapy, time window limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 64 publications
(80 reference statements)
0
7
0
3
Order By: Relevance
“…The prompt and correct stratification of stroke patients is decisive for the choice of the optimal therapy [22,23]. For acute stroke however numerous studies revealed inadequate interpretation of brain ct scans by acute care physicians [24,25] and even by experienced clinicians [26].…”
Section: Discussionmentioning
confidence: 99%
“…The prompt and correct stratification of stroke patients is decisive for the choice of the optimal therapy [22,23]. For acute stroke however numerous studies revealed inadequate interpretation of brain ct scans by acute care physicians [24,25] and even by experienced clinicians [26].…”
Section: Discussionmentioning
confidence: 99%
“…TIMI grades 2Y3 are pertinent in that revascularization is essential to achieve good outcomes. The modern stroke imaging using multimodal magnetic resonance imaging (MRI) and CT that provide information on occlusion type, penumbral tissue, and unsalvageable infarct core, which are an integral part of the standard of care, were not available at the seven hospitals involved, so this information was not available for analysis (Eckert, 2009;Tarr et al, 2010). However, the above study was limited for the following reasons.…”
Section: Review Ofmentioning
confidence: 99%
“…Cerebral ischemic stroke (CIS) is one of the leading causes of death worldwide; it has the characteristics of high morbidity, lethality, disability, and recurrence rate [ 1 3 ]. The related researches and reports have revealed that cerebral ischemia and reperfusion (I/R) injury (CIRI) is involved in energy metabolism disorders [ 4 ], oxidative stress [ 5 ], Ca 2+ overload, excitatory neurotransmitters, apoptosis, and necrosis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic stroke is a complex pathological process with multiple mechanisms [ 1 3 ]. Many pharmacological agents have been investigated for years, though with limited clinical success.…”
Section: Introductionmentioning
confidence: 99%